2003
DOI: 10.1093/clipsy.bpg024
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Meta-Analysis of Psychotherapy for Bulimia Nervosa.

Abstract: We report a multidimensional meta‐analysis of psychotherapy trials for bulimia nervosa published between 1980 and 2000, including multiple variables in addition to effect size such as inclusion and exclusion, recovery, and sustained recovery rates. The data point to four conclusions. First, psychotherapy leads to large improvements from baseline. Approximately 40% of patients who complete treatment recover completely, although 60% maintain clinically significant posttreatment symptoms. Second, individual thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 63 publications
(69 reference statements)
5
39
0
2
Order By: Relevance
“…Reliance on clinical judgment is at odds with a body of research on clinical versus actuarial prediction indicating that, on the whole, actuarial methods are superior, in part, because clinicians tend to identify too many exceptions to effective rules (Dawes, Faust, & Meehl, 1989). Controlled research has demonstrated that CBT and, secondarily, IPT, have the greatest efficacy for BN (National Institute for Clinical Excellence, 2004;Thompson'-Brenner et al, 2003), so these are the treatment decisions with the greatest likelihood for success. However, community clinicians are not basing treatment decisions on this evidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliance on clinical judgment is at odds with a body of research on clinical versus actuarial prediction indicating that, on the whole, actuarial methods are superior, in part, because clinicians tend to identify too many exceptions to effective rules (Dawes, Faust, & Meehl, 1989). Controlled research has demonstrated that CBT and, secondarily, IPT, have the greatest efficacy for BN (National Institute for Clinical Excellence, 2004;Thompson'-Brenner et al, 2003), so these are the treatment decisions with the greatest likelihood for success. However, community clinicians are not basing treatment decisions on this evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Two psychological interventions have demonstrated efficacy in improving eating disorder symptoms. Cognitivebehavior therapy (CBT) is generally considered to be the first-line treatment of choice for bulimia nervosa (BN; Thompson-Brenner, Glass, & Westen, 2003), and has also been applied to anorexia nervosa (AN; Vitousek, 2002) and binge eating disorder (BED; Wilfley et al, 2002). Interpersonal psychotherapy (IPT) has similar efficacy for BN as CBT, although its effects appear more slowly (Wilson & Pike, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We consulted with experts in their respective fields to ensure that the meta-analyses found were representative. In some cases, when a single meta-analysis was not Thompson-Brenner, Glass, & Westen, 2003;Vocks, 2010). No relevant meta-analyses could be identified for Academic Distress, as this is not a typical focus of psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] The potentially limited generalizability of findings from psychotherapy trials for BN due to high rates of exclusion based on study eligibility criteria has also been described. 36 Because eligibility criteria for this study did not specify exclusion criteria (e.g., comorbid Axis I and II psychopathology, previous hospitalizations) that are typical of controlled psychotherapy research, a strength may be its comparable representativeness with regard to patients admitted to residential treatment settings for eating disorders. Moreover, the attrition observed in this study, although suboptimal for its potential to introduce bias, is consistent with the high rates of study and treatment attrition reported across the eating disorder treatment literature.…”
Section: Discussionmentioning
confidence: 99%